An insight into small extracellular vesicles: Their roles in colorectal cancer progression and potential clinical applications. Issue 8 (12th December 2020) - He, Xuefeng; Zhong, Xinyang; Hu, Zijuan; Zhao, Senlin; Wei, Ping; Li, Dawei
Abstract: Colorectal cancer (CRC) is one of the most common cancers and a leading cause of mortality worldwide. Small extracellular vesicles (sEVs) are nano‐sized extracellular vesicles containing a variety of bioactive molecules, such as nucleic acids, proteins, lipids, and metabolites. Recent evidence from CRC has revealed that sEVs contribute to tumorigenesis, progression, and drug resistance, and serve as a tool for "liquid biopsy" and a drug delivery system for therapy. In this review, we summarize information about the roles of sEVs in the proliferation, invasion, migration, epithelial‐mesenchymal transition, formation of the premetastatic niche, and drug resistance to elucidate the mechanisms governing sEVs in CRC and to identify novel targets for therapy and prognostic and diagnostic biomarkers. Abstract : Colorectal cancer (CRC) is the third most commonly diagnosed cancer worldwide and patients with metastasis usually have a poor prognosis. Small extracellular vesicles (sEVs) have been identified to play a significant role in intercellular communication. sEVs released from different cells exert huge effects on CRC cell proliferation and metastasis. They could also serve as biomarkers for CRC diagnosis and prognosis and be a potential drug delivery system to treat CRC patients.